The Long-Run and Short-Run Effects of Brexit Referendum on the UK Economy - Drašković, Aleksandra; Potužák, Pavel; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
This thesis analyses impacts of the Brexit referendum on the economy of the United Kingdom. It aims at explaining the reasons and consequences of the Brexit decision as well as negotiations between the European Union and the United Kingdom. The main macroeconomic variables are analysed to see a true effect of the Brexit vote, which took place on 23rd June 2016. Particularly, real GDP and its growth rate are further explained, as well as labour productivity, trade, migration, the exchange rate, or inflation. Three models regarding consequences of the Brexit referendum are created. The first model, which tests the impact of the referendum on the growth rate of real GDP, proves to be significant, which means that the growth rate was influenced by the vote. The second model, which studies the effects on the level of uncertainty, shows that the level of uncertainty was not influenced by the referendum. The third model, which is concentrating on the growth rate of the exchange rate, shows to be also insignificant; meaning that the referendum did not have large effect. There is also strong correlation between the growth rate of the exchange rate and the level of uncertainty, between the growth rate of real GDP and uncertainty and between the growth rate of real GDP and the growth rate of the exchange rate.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses